Evidence-Informed Assessment and Practice in Child Welfare - Wodarski, John S.; Holosko, Michael J.; Feit, Marvin D. (Springer International Publishing : Imprint: Springer, 2015)
This practice-oriented text presents evidence-based assessment methods and interventions that have been extensively field-tested in child welfare settings. The contributors offer empirical and field insights, comprehensive treatment models, and curricula in key areas such as child maltreatment, substance abuse, parent training, social skills, and youth employment interventions. For the professional reader, the book offers real-world guidance on social work practice, from hiring opportunities within a system to promoting lasting change as families and their issues grow increasingly complex. These chapters also take significant steps toward future improvements in child protection systems as the field evolves toward being more coordinated, effective, and professional. Included in the coverage: Legal requisites for social work practice in child abuse and neglect. The integrated model for human service delivery in child welfare. Risk assessment: issues and implementation in child protective services. Substance use and abuse: screening tools and assessment instruments. The process of intervention with multi-problem families. Preventative services for children and adolescents. Its multi-level approach makes Evidence-Informed Assessment and Practice in Child Welfare an essential professional development text for social workers, particularly those new to the job, as well as a progressive blueprint for social work administrators.